Distribution of a Random Continued Fraction with Markov Elements - Vynnyshyn, Ya. F. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We study the structure of the distribution of a random variable such that the elements of its continued fraction form a Markov chain of order m. It is proved that an absolutely continuous component is absent from such distributions.